John Hume in America : from Derry to DC - Fitzpatrick, Maurice, 1981- (University of Notre Dame Press, 2019)
"In John Hume in America: From Derry to DC and its accompanying documentary, In the Name of Peace: John Hume in America, Maurice Fitzpatrick chronicles the rise of John Hume from the riot-torn streets of Northern Ireland to his work with American presidents, from Jimmy Carter to Bill Clinton, and the United States Congress to leverage U.S. support for peace in Northern Ireland. Hume is widely considered the architect of the Northern Ireland peace process, and he engaged the attention and assistance of the "Four Horsemen"--Thomas "Tip" O'Neill, Daniel Patrick Moynihan, Hugh Carey, and Ted Kennedy--to his cause, lending his effort worldwide credibility and putting significant pressure on the British and Irish governments to strive for peace. Supported by the Hume family, Fitzpatrick's critical work is the missing piece in the jigsaw of Hume's political life, tracing his philosophy of non-violence during the Civil Rights movement to his indispensable work with allies in the United States towards the creation of a new political framework in Northern Ireland. Both the book and its companion documentary will be of keen interest to historians and students of political science and Irish, peace, and conflict studies, as well as non-academic audiences."--